Oxidation Performance of Nano-Layered (AlTiZrHfTa)Nx/SiNx Coatings Deposited by Reactive Magnetron Sputtering; Materials; Vol. 17, iss. 12 - Touaibia D. E. Djallel Eddine; Achache S. Sofiane; Bouissil A. Abdelhakim; Parent F. Fabrice; Ghanbaja J. Jaafar; Gorbunova A. Alina; Postnikov P. S. Pavel Sergeevich; Chehimi M. Mohamed; Schuster F. Frederic; Sanchette F. Frederic; El G. M. Garah Mohamed (2024, 2024)
Title screen